Invasive and noninvasive markers of human skeletal muscle mitochondrial function - Mancilla, Rodrigo; Pava‐Mejia, Diego; Polanen, Nynke; Wit, Vera; Bergman, Maaike; Grevendonk, Lotte; Jorgensen, Johanna; Kornips, Esther; Hoeks, Joris; Hesselink, Matthijs K. C.; Schrauwen‐Hinderling, Vera B. (Physiological reports, 2023)
Mitochondria are organelles that fuel cellular energy requirements by ATP formation via aerobic metabolism. Given the wide variety of methods to assess skeletal muscle mitochondrial capacity, we tested how well different invasive and noninvasive markers of skeletal muscle mitochondrial capacity reflect mitochondrial respiration in permeabilized muscle fibers. Nineteen young men (mean age: 24 ± 4 years) were recruited, and a muscle biopsy was collected to determine mitochondrial respiration from permeabilized muscle fibers and to quantify markers of mitochondrial capacity, content such as citrate synthase (CS) activity, mitochondrial DNA copy number, TOMM20, VDAC, and protein content for complex I–V of the oxidative phosphorylation (OXPHOS) system. Additionally, all participants underwent noninvasive assessments of mitochondrial capacity: PCr recovery postexercise (by 31P‐MRS), maximal aerobic capacity, and gross exercise efficiency by cycling exercise. From the invasive markers, Complex V protein content and CS activity showed the strongest concordance (Rc = 0.50 to 0.72) with ADP‐stimulated coupled mitochondrial respiration, fueled by various substrates. Complex V protein content showed the strongest concordance (Rc = 0.72) with maximally uncoupled mitochondrial respiration. From the noninvasive markers, gross exercise efficiency, VO2max, and PCr recovery exhibited concordance values between 0.50 and 0.77 with ADP‐stimulated coupled mitochondrial respiration. Gross exercise efficiency showed the strongest concordance with maximally uncoupled mitochondrial respiration (Rc = 0.67). From the invasive markers, Complex V protein content and CS activity are surrogates that best reflect skeletal muscle mitochondrial respiratory capacity. From the noninvasive markers, exercise efficiency and PCr recovery postexercise most closely reflect skeletal muscle mitochondrial respiratory capacity. There are numerous methods available to measure human skeletal muscle mitochondrial function and oxidative capacity; however, these various readouts are not always in full agreement with each other. We examined which commonly used invasive (VDAC, mtDNA, TOMM20, CS, and OxPhos) and noninvasive (PCr recovery, VO2max, and exercise efficiency) markers of skeletal muscle mitochondrial capacity correlate best with the mitochondrial respiratory capacity in permeabilized human muscle fibers. From the invasive markers, Complex V protein content and CS activity are surrogates that best reflect skeletal muscle mitochondrial respiratory capacity. From the noninvasive markers, exercise efficiency, and PCr recovery postexercise most closely reflect skeletal muscle mitochondrial respiratory capacity. These results are of relevance for studies that aim to investigate skeletal muscle mitochondrial function in humans but do not possess the high‐resolution respirometry methodology and/or are unable to obtain muscle biopsies.